Modelling low pay transition probabilities, accounting for panel attrition, non-response, and initial conditions - Lorenzo Cappellari; Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2004)
We model annual low pay transition probabilities taking account of three potentially endogenous selections: two sample drop-out mechanisms (panel attrition, non-employment) and initial conditions (base-year low pay status). This model, and variants that ignore one or more of these selection mechanisms, are fitted to data for men from the British Household Panel Survey. Tests of the ignorability of the endogenous selection mechanisms suggest that economic selection mechanisms such as initial conditions and retention of employment are more important than the survey selection mechanism (attrition). However, consistent with related US research, relatively simple models provide estimates of covariate effects that differ little from the estimates from the complicated models.
Keywords: 330